2012
DOI: 10.1016/j.physbeh.2011.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Fat discrimination: A phenotype with potential implications for studying fat intake behaviors and obesity

Abstract: Variations in fat preference and intake across humans are poorly understood in part because of difficulties in studying this behavior. The objective of this study was to develop a simple procedure to assess fat discrimination, the ability to accurately perceive differences in the fat content of foods, and assess the associations between this phenotype and fat ingestive behaviors and adiposity. African-American adults (n=317) were tested for fat discrimination using 7 forced choice same/different tests with Ita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 40 publications
3
44
0
1
Order By: Relevance
“…The relationship between sensory fat perception and predisposition to weight gain has been shown in recent adult human studies (Liang et al, 2012;Stewart et al, 2010;Stewart et al, 2011). This relationship outlines the remarkable difference in obese and lean subjects with respect to fat intake and taste sensitivity.…”
Section: Fat Tastementioning
confidence: 80%
See 2 more Smart Citations
“…The relationship between sensory fat perception and predisposition to weight gain has been shown in recent adult human studies (Liang et al, 2012;Stewart et al, 2010;Stewart et al, 2011). This relationship outlines the remarkable difference in obese and lean subjects with respect to fat intake and taste sensitivity.…”
Section: Fat Tastementioning
confidence: 80%
“…Similarly, a high-fat diet decreased the taste sensitivity to oleic acid in lean, but not obese patients (Stewart & Keast, 2012). These observations suggest that a lack of sensitivity to fat taste increases fat intake, and may partly explain why obese adult individuals seem to consume fatty foods more frequently than lean patients (Liang et al, 2012;Stewart et al, 2011).…”
Section: Fat Tastementioning
confidence: 81%
See 1 more Smart Citation
“…The fungiform papillae hold active taste cells and are densely innervated by trigeminal (somatosensory) nerves that function to relay information to the brain about textural sensations of food, including the oiliness, creaminess, and mouth-feel (92). Regardless of PROP status, other studies have reported that reduced ability to perceive dietary fat is associated with increased acceptance and intake of higher-fat foods (83,125,126). We have speculated that nontasters might compensate for reduced fat perception by consuming higher-fat foods in the diet that provide additional oral stimulation and sensory input (74).…”
Section: Fat-containing Foodsmentioning
confidence: 99%
“…This cluster contained more men, more consumers with a higher BMI, and more consumers with a high frequency of butter usage. Previous research has indicated that fat nondiscriminators may have greater abdominal adiposity compared with fat discriminators (Liang et al, 2012). The smallest cluster (12%) rated all butter and spread samples lower than the other clusters; this cluster had very few frequent butter consumers.…”
Section: Discussionmentioning
confidence: 74%